Documentation of ritual plants used among the Aceh tribe in Peureulak, East Aceh District, Indonesia - Imam Hadi Sutrisno; BACHTIAR AKOB; ZIDNI ILMAN NAVIA; NURAINI NURAINI; ADI BEJO SUWARDI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Sutrisno IH, Akob B, Navia ZI, Nuraini, Suwardi AB. 2020. Documentation of ritual plants used among the Aceh tribe in Peureulak sub-district, East Aceh, Indonesia. Biodiversitas 21: 4990-4998. Traditional ceremonies as part of human cultural products at a practical level cannot be separated from the use of natural resources, mainly plants. Concerning the use of plants in traditional ceremonies, the knowledge and use of plants by the community are decreasing. This study aims to document the ritual plants used by the Aceh tribe in the East Aceh district of Indonesia. The study was conducted in Peureulak sub-districts, East Aceh district, Indonesia. A field survey was involved 125 respondents were selected using random sampling. The interview used a questionnaire including plant species, vernacular names, uses, parts use, and ritual tradition. A total of 51 ritual plant species consisting of 47 genera and 34 families was used as ritual ceremonies in the study area. Ninety-two percent were cultivated and 8% were found to be growing wild. Most of the plants used for wedding ceremonies (18 species), followed by birth ceremonies (8 species), funeral ceremonies (5 species), and pregnancy ceremony (3 species). Socio-cultural aspects can be considered as being used for the conservation of ritual plants in the East Aceh region.